NOT JUST DRYNESS: A REVIEW OF PERIPHERAL NEUROPATHY IN PRIMARY SJÖGREN’S SYNDROME - Anna Rupińska,; Agnieszka Floriańczyk,; Hanna Skarakhodava,; Ewa Romanowicz,; Aleksandra Kołdyj,; Agnieszka Ozdarska,; Adrian Krzysztof Biernat,; Marcin Lampart,; Katarzyna Kozon,; Kamila Krzewska, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Primary Sjögren’s syndrome (pSS) is a chronic systemic autoimmune disease primarily affecting exocrine glands, but it can also involve the peripheral nervous system (PNS). Peripheral neuropathy (PN) is a diverse extraglandular manifestation of pSS, with distal axonal polyneuropathy and sensory neuronopathy (ganglionopathy) being the most prevalent subtypes. PN symptoms often precede the diagnosis of pSS, posing a diagnostic challenge.Materials and methods: An electronic literature search was performed using PubMed. Search terms included ‘primary Sjögren’s syndrome (pSS)’, ‘peripheral neuropathy’, ‘neurological involvement’, ‘Neuro-Sjogren’, ‘polyneuropathy’, ‘small fibre neuropathy’ as keywords. This review focused on articles published in English from their inception until 2025.Conclusions: Diagnostic approaches combine clinical evaluation, electrophysiological testing, and other procedures such as nerve and skin biopsies. Treatment remains challenging due to the heterogeneity of neuropathic presentations and limited evidence guiding clinical decisions. Corticosteroids are primarily effective in neuropathies associated with vasculitis. Immunosuppressive agents and intravenous immunoglobulin (IVIG) are also commonly used. In addition, effective symptomatic management of neuropathic pain plays an important role in the overall care of the patient. As evidence on the treatment of PN in pSS is limited further research is needed. Early detection and individualized treatment are essential to improve patients’ quality of life.